Caribbean economic recessions in historical perspective : address - Bourne, Compton (CDB [St. Michael]BB, 2008)
Deals with the historical record of economic recession in the Caribbean during the period 1900-2004. Focuses particularly on the Great Depression, 1929-35 and 1938-40, as well as on the modern, post-independence period starting in the 1960s.